Pemberdayaan Masyarakat Melalui Pelatihan Pembuatan Sediaan Gel Antijerawat Berbahan Herbal Lokal - Suharyanisa Suharyanisa; Widya Fitri; Nuranti Rumela; Betharina br Tarigan (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Acne is a common skin problem caused by excessive growth of Staphylococcus aureus on the skin due to increased sebum production. Dragon scale leaves (Drymoglossum piloselloides) contain active compounds such as saponins, phenols, tannins, and flavonoids, which have antibacterial and anti-inflammatory properties. This community service program aims to enhance public knowledge about the utilization of dragon scale leaf extract in acne gel formulations. The activities included education, a demonstration of gel preparation, and an evaluation of training effectiveness through pre-tests and post-tests. The evaluation results showed an increase in participant understanding from 20% to 75%, exceeding the targeted improvement. Active community participation indicates a strong interest in utilizing herbal plants as an alternative skincare solution, highlighting the potential for further development.